TECHNOLOGY LEADERSHIP IN INDONESIAN JUNIOR HIGH SCHOOLS DURING THE POST-COVID ERA: A CASE STUDY OF SPIRITUAL DIMENSIONS - Setia, Shinta (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2025)
COVID-19 in Indonesia necessitated a shift from traditional face-to-face learning to technology-based distance learning. This transition also redefined the role of school principal who must lead change and work in new ways. This study aims to explore the new role of the principal as a technology leader and develop a technology leadership model in learning in the new normal era. Employing a qualitative approach with a single case study method, the study involved 20 participants, including 5 principals, 5 vice principals, 5 IT coordinators, and 5 subject teachers from five public junior high schools (SMP Negeri) in Surabaya, Indonesia.. The findings study show that school principal has a key role in keeping the school functioning well in the new normal era. This findings highlight the latest model of technology leadership in education by developing 5 dimensions of technology leadership from NETS-EL 2018 into 6 dimensions. The spiritual dimension makes technology leaders and teachers are more effective in leading schools during and after COVID-19. These findings specifically contribute to the development of a technology leadership framework and generally complement existing leadership theories.